Mobile peoples - permanent places : nomadic landscapes and stone architecture from the Hellenistic to early Islamic periods in north-eastern Jordan /: nomadic landscapes and stone architecture from the Hellenistic to early Islamic periods in north-eastern Jordan. (2019) - Huigens, Harmen O
No abstract available